The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.21203/rs.3.rs-2158307/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolomic Profiling, In Vitro Antioxidant and Cytotoxicity Properties of Caulerpa racemosa : Functional Food of the Future from Algae

Abstract: Marine macroalgae are nutraceuticals rich in nutritional profile and secondary bioactive metabolites. However, they have varied nutritional and biochemical qualities due to a variety of reasons. This study aimed to determine the phytochemical profile and biological activities of Caulerpa racemosa, edible green algae also known as Sea grapes. The study successfully identified secondary metabolites through metabolomic profiling untargeted by LC-HRMS as well as a bioactive peptide. In addition, antioxidant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…The dried simplicia was extracted using either the hot or the cold method [ 11 ]. Maceration represents the cold way, while soxhlet represents the hot way.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dried simplicia was extracted using either the hot or the cold method [ 11 ]. Maceration represents the cold way, while soxhlet represents the hot way.…”
Section: Methodsmentioning
confidence: 99%
“…About two-thirds of Indonesia’s territory is in the form of the sea, and it is famous as one of the world’s mega-diversity areas, with more than 555 macroalgae species having been identified in its ocean areas. In addition, most of Indonesia’s islands are located within the Coral Triangle, which has been identified as an area with a very high diversity of Caulerpa [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the safety profile of C. racemosa has been investigated using the MTT assay in another study, and in that study, the LC 50 value for a macerated extract of C. racemosa (EM) in 24 h of incubation is 914.78 μg/ml. In terms of cytotoxicity, it was observed that C. racemosa was safe to be potentially developed into various products ( Nurkolis et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the existence of photosynthetic pigments, green algae are members of the Chlorophyta phylum of the Plantae kingdom ( 15 ). As stated above, seaweed has several health-benefiting potentials ( 16 18 ). Numerous sulfated and carboxylated polysaccharides, including alginate, ulvan, and fucoidan, as well as carotenoids, phenolic compounds, tocopherols, and peptides, are among the many bioactive substances found in seaweed ( 19 ).…”
Section: Green Seaweeds and Anticancer Propertiesmentioning
confidence: 99%